Radiographically confirmed community-acquired pneumonia in hospitalized adults due to pneumococcal vaccine serotypes in Sweden, 2016–2018—The ECAPS study - Hansen, Karin; Rünow, Elisabeth; Torisson, Gustav; Theilacker, Christian; Palmborg, Andreas; Pan, Kaijie; Jiang, Qin; Southern, Jo; Beavon, Rohini; Gessner, Bradford D.; Riesbeck, Kristian; Ahl, Jonas (Frontiers in Public Health, 2023)
Objectives In Sweden, pneumococcal serotype distribution in adults with community-acquired pneumonia (CAP) and potential coverage of currently licensed pneumococcal conjugate vaccines (PCVs) is unknown. Methods During 2016–2018, patients aged ≥18 years hospitalized with radiologically confirmed (RAD+) CAP were enrolled at Skåne University Hospital in a study on the etiology of CAP in Sweden (ECAPS). Urine samples and blood cultures were collected per-protocol. Streptococcus pneumoniae (Spn) culture isolates were serotyped and urine samples tested for the pan-pneumococcal urinary antigen (PUAT) and multiplex urine antigen detection (UAD) assay, detecting 24 serotypes. Results Analyses included 518 participants with RAD+CAP; 67.4% were ≥65 years of age, 73.4% were either immunocompromised or had an underlying chronic medical condition. The proportion of CAP due to Spn identified by any method was 24.3% of which 9.3% was detected by UAD alone. The most frequently identified serotypes were 3 (26 cases, 5.0% of all CAP), and 8, 11A and 19A (10 cases each, 1.9%). In individuals aged 18–64 and ≥65 years, respectively, PCV20 serotypes contributed to 35 of 169 (20.7%) and 53 of 349 cases of all CAP (15.2%), and PCV13 serotypes caused 21 of 169 (12.4%) and 35 of 349 (10.0%) cases. PCV15 coverage was 23 of 169 (13.6%) and 42 of 349 (12.0%) in individuals aged 18–64 and ≥65 years, respectively. Overall, PCV20 increases the coverage of all CAP from 10.8% (PCV13) to 17.0%. Conclusion Compared to earlier pneumococcal vaccines, PCV20 expands the coverage of all-cause CAP. Routine diagnostic tests underestimate the proportion of CAP caused by Spn.